Success factors for the commercialisation of Gas-to-Liquids technology - K. E. Meleloe; D. R. Walwyn (South African Journal of Business Management, 2016)
Notwithstanding the 2014/15 plunge in crude oil prices, Gas-to-Liquids (GTL) technology has been acclaimed as an important alternative to existing sources of liquid fuels, leading to significant efforts by many oil and gas companies, including Sasol, Shell, Axens, BP, GTL.F1, JOGMEC and Rentech, to develop GTL processes. However, only two companies, namely Sasol and Shell, have been successful with these endeavours. In this research, a mixed methods approach has been used to explore the reasons for this success, including the influence of commercial and technical factors. A framework consisting of five commercialisation success factors was developed and an analytical hierarchy process used to compare and rank the different success factors following interviews with a diverse set of role players in the GTL industry. It is clear that large-scale GTL projects require massive capital investment and carry large techno-economic risks. Moreover, an accurate return on investment is impossible to predict due to uncertainties in technology performance and market factors. As a consequence, project developers and financiers mitigate their risk by securing co-investment from GTL operators. Shell and Sasol dominate the GTL industry not necessarily because their technologies offer higher returns, but because they have jointly invested in GTL projects, an approach which subscribes to a model of technology push with risk sharing. It is recommended that other licensors should pursue the large scale validation of their technology at an existing syngas facility as a strategy to gain entry into the GTL market.
Keywords: 650